2020
DOI: 10.1101/2020.04.29.20085449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary Results of Seroprevalence of SARS-CoV-2 at Community Clinics in Tokyo

Abstract: Serological evaluation with SARS-CoV-2 specific IgG antibody will be an alternative way to know the pandemic of novel coronavirus disease (COVID-19) if the capacity for diagnostic PCR test is limited. The point-of-care test to detect SARS-CoV-2 specific IgG antibody in peripheral blood (n =202) was performed in two community clinics in Tokyo, Japan. The overall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…The majority of studies was conducted in Europe (n=31), and then in North America (n=9), Asia (n=6), and Africa (n=3). In particular, nine studies was conducted in USA [ 14 , 15 , 24 , 26 , 27 , 29 , 32 , 34 , 40 ], eight studies in Italy [ 23 , 28 , 30 , 36 , 44 , 45 , 56 , 57 ], seven studies in United Kingdom [ 16 , 17 , 20 , 25 , 33 , 59 , 61 ], five studies in Germany [ 21 , 35 , 42 , 43 , 46 ], four studies in Spain [ 31 , 38 , 49 , 52 ], and three studies in and Japan [ 53 , 58 , 62 ], Belgium [ 18 , 19 , 22 ] and China [ 47 , 48 , 51 ]. Twenty-nine studies did not report the response rate [ [15] , [16] , [17] , 20 , 24 , [26] , [27] , [28] , [29] , [30] , [32] , [33] , [34] , 38 , [40] , [41] , [42] , [43] , 45 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies was conducted in Europe (n=31), and then in North America (n=9), Asia (n=6), and Africa (n=3). In particular, nine studies was conducted in USA [ 14 , 15 , 24 , 26 , 27 , 29 , 32 , 34 , 40 ], eight studies in Italy [ 23 , 28 , 30 , 36 , 44 , 45 , 56 , 57 ], seven studies in United Kingdom [ 16 , 17 , 20 , 25 , 33 , 59 , 61 ], five studies in Germany [ 21 , 35 , 42 , 43 , 46 ], four studies in Spain [ 31 , 38 , 49 , 52 ], and three studies in and Japan [ 53 , 58 , 62 ], Belgium [ 18 , 19 , 22 ] and China [ 47 , 48 , 51 ]. Twenty-nine studies did not report the response rate [ [15] , [16] , [17] , 20 , 24 , [26] , [27] , [28] , [29] , [30] , [32] , [33] , [34] , 38 , [40] , [41] , [42] , [43] , 45 , 47 , 48 ,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies did not report the response rate [ [15] , [16] , [17] , 20 , 24 , [26] , [27] , [28] , [29] , [30] , [32] , [33] , [34] , 38 , [40] , [41] , [42] , [43] , 45 , 47 , 48 , 50 , 51 , [55] , [56] , [57] , [58] , [59] , 62 ], nine studies did not report HCWs’ age [ 17 , 18 , 21 , 23 , 32 , 33 , 36 , 41 , 48 ], eight studies did not report sex distribution [ 16 , 18 , 21 , 25 , 32 , 33 , 41 , 48 ] and five studies did not report data collection time [ 17 , 36 , 43 , 48 , 56 ]. Females’ percentage ranged from 35% [ 62 ] to 88.5% [ 51 ] and was higher in 41 studies, while in three studies males’ percentage was higher. Mean age of HCWs ranged from 31.2 [ 51 ] years to 47.9 years [ 57 ], while sample size ranged from 25 [ 40 ] to 40,329 HCWs [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies only looked at COVID-19 incidence, rather than prevalence of antibodies, and were thus considered potentially unreliable as population estimates ( 19 ). The most common reason for exclusion was selection bias – many studies only looked at targeted populations in their seroprevalence data, and thus could not be used as population estimators of IFR ( [14] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ). For some data, it was difficult to determine the numerator (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…77 Seroprevalence of SARS-CoV-2 infection in health care workers from two community clinics in Japan observed 9.1% positivity rate in comparison to the overall rate of 5.9%. 78 Samples collected randomly from health professionals in Spain depicted 11.2% of cumulative prevalence in antibody quantification and 97-100% positive predictive value. 79 A study reported from Italy showed 5.25% seropositivity within the asymptomatic health care providers.…”
Section: A Hunt For Asymptomatic Casesmentioning
confidence: 99%